In-situ characterization of cake layer fouling during crossflow microfiltration of oil-in-water emulsion - Tanudjaja, Henry Jonathan (2021)
In view of membrane-filtration being a promising means for treating the large volumes of oily wastewater, much efforts have been dedicated to understanding membrane fouling by oil emulsions. However, the understanding on cake fouling, which is the governing form of fouling throughout filtration, by oil emulsions remain poorly understood. To bridge this gap, this study focused on characterizing the evolution of the oil-emulsion cake layer characteristics on hollow fiber (HF) membranes in real time using the direct observation through the membrane (DOTM) technique. The more well-studied latex particles were studied alongside to provide a benchmark for comparison. Despite the same feed concentration and crossflow velocity used, the transmembrane pressure (TMP) and cake layer resistance magnitudes were greater for oil emulsion than for latex particles at the same permeate flux. DOTM images revealed that this was linked to the following behaviors: (i) oil tended to deposit as a moving cake layer, whereas latex as scattered deposits; and (ii) oil gave a thinner yet denser cake layer. Moreover, it was observed that the cake thickness and porosity fluctuated significantly with respect to permeate volume for the oil emulsions, because the moving cake layer gave greater variations of cake thicknesses along the membrane. Finally, the interfacial interaction energy predicted by the XDLVO model gave higher oil-membrane and oil-oil affinities compared to that of latex, which underlie respectively the more extensive fouling and denser cake exhibited by oil. The unique characteristics of the cake layer of oil emulsion vis-à-vis the well-studied particulate foulant (i.e., latex) shown here provides new perspectives on the monitoring and control of oil fouling.